The Effect of Motor Ability Level on Taekwondo Kick Learning Outcome through Reciprocal Teaching Style - Juniar, Dicky Tri (Universitas Pendidikan Indonesia, 2019)
The purpose of this research was to determine the effect of reciprocal teaching style and high motor ability on the results of dolyo chagi kicks. The method used in this research was the experimental method. The sampling technique used was simple random (random assignment) technique. The result of this research is that there was a significant influence of reciprocal teaching style for students who have high motor ability on dolyo chagi kick learning outcomes (thit.=12,77 ttab. 3,63). The implication of this research for students is that the students have a better accomplishment in studying Taekwondo when they are supported by a high motor ability. For a lecturer or a teacher, it can be a consideration in choosing a teaching style that is suitable for the characteristics of the students.Â Â AbstrakTujuan dari penelitian ini adalah untuk mengetahui pengaruh gaya mengajar resiprokal dan motor ability tinggi terhadap hasil tendangan dolyo chagi. Metode yang digunakan pada penelitian ini adalah metode eksperimen. Pengambilan sampel yang digunakan adalah acak sederhana (random assignment). Hasil dari penelitian ini adalah terdapat pengaruh yang signifikan gaya mengajar resiprokal untuk mahasiswa yang memiliki motor ability tinggi terhadap hasil belajar tendangan dolyo chagi (thit.=12,77 ttab. 3,63). Implikasi dari penelitian ini bagi mahasiswa adalah mahasiswa akan semakin berprestasi dalam belajar Taekwondo apabila ditunjang dengan motor ability yang tinggi dan bagi dosen atau guru adalah menjadi pertimbangan dalam memilih gaya mengajar yang sesuai dengan karakteristik peserta didik.Â